Community Engagement in Development Planning in Jabon District - Ghufron, Akhmad; Agustina, Isna Fitria (Indonesian Journal of Cultural and Community Development, 2024)
Background: Community participation is essential for effective development planning in rural areas. Specific Background: This study examines participation in development planning within a particular village. Knowledge Gap: Although existing literature recognizes community involvement, disparities in participation among different societal groups remain underexplored. Aims: The research aims to analyze community participation levels and highlight engagement differences. Results: Findings reveal uneven participation in oversight processes, with certain groups more engaged, potentially sidelining the interests of less active segments. Novelty: This study emphasizes the need for inclusive strategies to ensure diverse community voices are heard. Implications: Results call for initiatives that promote broader engagement in oversight activities, facilitating equitable representation and effective development planning that addresses the challenges of marginalized groups. Highlights : Engagement Disparities: Participation levels vary significantly among community groups. Inclusive Strategies: Effective planning requires ensuring all voices are heard. Representation Challenges: Underrepresented segments may have their interests overlooked. Keywords: community participation, development planning, oversight processes, engagement disparities, inclusive strategies